Employment and earnings trajectories before and after sickness absence due to major depressive disorder: a nationwide case–control study. (13th October 2020) - Hakulinen, Christian; Böckerman, Petri; Pulkki-Råback, Laura; Virtanen, Marianna; Elovainio, Marko
Abstract : Objectives: To examine employment and earnings trajectories before and after the first sickness absence period due to major depressive disorder (MDD). Methods: All individuals (n=158 813) in Finland who had a first sickness absence period (lasting longer than 9 days) due to MDD between 2005 and 2015 were matched with one randomly selected individual of the same age and gender with no history of MDD. Employment status and earnings were measured using register-based data annually from 2005 to 2015. Generalised estimating equations were used to examine the trajectories of employment and earnings before and after MDD diagnosis in men and women separately. Results: Sickness absence due to MDD was associated with increased probability of non-employment during and after the year of the first sickness absence period. In men, but not in women, the probability of being employed was lower 5 years before the sickness absence period due to MDD. When compared with the individuals in the control group, men had around 34% and women 15% lower earnings 1 year, and 40% and 23%, respectively, 5 years, after the first sickness absence period due to MDD. More severe MDD and longer duration of sickness absence period were associated with lower probability of being employed. Conclusions: Sickness absence due to MDD was associated with considerable reduction in employment and earnings losses. For men and individuals with more severe MDD, this reduction was before the first sickness period. This supports a reciprocal association between employment and earnings with MDD.